The Development of smallholder rubber in Thailand - Nikomrat Sunthorn (Proceedings : Indonesian Rubber Conference and IRRDB symposiun 2000 Indonesian Rubber Research Institute, Bogor, Indonesia, 12-14 September 2000.V.1.pp.16-22.)
Rubber was introduced into Thailand in 1899, thus 101 years ago. Structurally, the majority (93;) of the rubber plantation owned by the smallholder, the rest being run by estate sector. Rubber plantations in Thailand were developed from time to time. At the beginning, rubber plantations in South and Southeast of Thailand grown by the low yielding native rubber clone. In 1960 the government established the Office of Rubber Replanting Aid Fund (ORRAF) to replant the old and low yielding trees by the high yielding tree. From 1987 onward, the government introduced rubber to the new area in the Northeast. Rubber, finally, becomes the important cash crop inthis region. Through the replanting activity, rubber production of Thailand as well as an income of the smallholder was highly increased, Thailand finally, become the world largest NR producer and export since 1991. Rubber price in the world market fluctuates from time to time. The rubber price, in general, is quite low which highly effects standard living of the smallholders. To increase the bargaining powe of the smallholder as well as to improve the quality of rubber, several organizations of rubber smallholders were developed by the assistant of the government sectors. Such organizations are group processing, group marketing organization, rubber smallholder co-operatives and and provincial smallholder association. The government also develops marketing system in Thailand to assist the rubber smallholder. Several marketing systems are developed namely: Auction Market, Central rubber market and Direct Trading. More detail of the above development activities are discussed.
Keywords: Smallholder rubber; Thailand